Geolocation with respect to personal privacy for the Allergy Diary app - a MASK study - Samreth, Darren; Pfaar, Oliver (World Allergy Organization journal, 2018)
Background Collecting data on the localization of users is a key issue for the MASK (Mobile Airways Sentinel networK: the Allergy Diary) App. Data anonymization is a method of sanitization for privacy. The European Commission’s Article 29 Working Party stated that geolocation information is personal data. To assess geolocation using the MASK method and to compare two anonymization methods in the MASK database to find an optimal privacy method. Methods Geolocation was studied for all people who used the Allergy Diary App from December 2015 to November 2017 and who reported medical outcomes. Two different anonymization methods have been evaluated: Noise addition (randomization) and k-anonymity (generalization). Results Ninety-three thousand one hundred and sixteen days of VAS were collected from 8535 users and 54,500 (58.5%) were geolocalized, corresponding to 5428 users. Noise addition was found to be less accurate than k-anonymity using MASK data to protect the users’ life privacy. Discussion k-anonymity is an acceptable method for the anonymization of MASK data and results can be used for other databases.
Gesehen am 02.12.2020
Available online 1 January 2019